Syntactic and semantic features of ditransitive verbs in English and their Vietnamese equivalents in a literature work / Do Viet Dinh; Supervisor: Assoc.Prof. Dr. Le Van Thanh - Do, Viet Dinh
The stduy focus on solving the mảo question of what the primary similarirties and differences between the ditransitive verbs in English and their Vietnamese equivalents in a literatural work in terms of syntactic and semantic features. An action research was carried out to answer the research questions: (1) What are syntactic and semantic features of ditransitive verbs in English? (2) What are the the similarities and differences between ditransitive verbs in English and their Vietnamses equivalents in a literature work? (3) What implication is drawn for learning ditransitive verbs effectively? The data from bookd, newspapers, articles, magazines on the internet and in daily lives are collected and analysed by the writer and are studied in the light of semantic and syntactic features. From the result of the study, it is attempted to have better understanding the ditransitive verbs in English and their Vietnamese equivalents when it comes to semantics and syntactics with the hope that it will help learners and readers to recognise the importance of mastering these verbs in both English and Vietnamese. Additionally, the study will help teachers be aware of the differences between the two languages and give emphasis when teaching so that their students can remember and avoid the mistakes from the beginning. Teachers should draw out some common mistakes and errors, which often cause troubles to students and ask students to note down to remember. Therefore, the study bears a great potential of becoming a basis for other authors to make more intensive researches in the future.